Dinosaur explorers. #4, Trapped in the Triassic - Redcode (Comic writer); Albbie (Comic writer) (Papercutz, 2019)
In their time travel experiment the Dinosaur Explorers find themselves in the Triassic. When Emily suddenly quits the group and runs away, the rest of the gang goes out to look for her, only to find Emily's chewed-up shoe. Now the search is really on to find Emily and escape the Triassic Period alive.